Knowledge for Medicine and Health Care - van Bemmel, Jan H. (Methods of Information in Medicine, 2005)
Dr. Donald A. B. Lindberg, Director of the U.S. National Library of Medicine, received an honorary doctorate from UMIT, the University for Health Sciences, Medical Informatics and Technology in Innsbruck, Tyrol. The celebration took place on September 28, 2004 at an academic event during a conference of the Austrian, German, and Swiss Societies of Medical Informatics, GMDS2004. Dr. Lindberg has been a pioneer in the field of computers in health care from the early 1960s onwards. In 1984 he became the Director of the National Library of Medicine in Bethesda, the world’s largest fully computerized biomedical library. Dr. Lind-berg has been involved in the early activities of the International Medical Informatics Association (IMIA), among others being the chair of the Organizing Committee for MEDINFO 86 in Washington D.C. He was elected the first president of the American Medical Informatics Association (AMIA), and served as an editor of Methods of Information in Medicine.
Keywords: Medical informatics; IMIA; AMIA; NLM; MedLine